Sulfur Containing High Refractive Index Poly(arylene Thioether)s and Poly(arylene Ether)s - Mazumder, Kajari; Komber, Hartmut; Bittrich, Eva; Voit, Brigitte; Banerjee, Susanta (Macromolecules, 2022)
A series of novel sulfur containing high refractive index linear and branched poly(arylene thioether)s and linear poly(arylene ether)s were synthesized via nucleophilic substitution reactions. The sulfur content was varied in each polymer structure, and the physico-chemical properties of the polymer were investigated with respect to sulfur and aromatic content. The polymers prepared exhibited transparency as high as 90% in the visible region and an RI of more than 1.70 at 589 nm. These properties along with high thermal stability (Td5% up to 530 °C), excellent mechanical properties with tensile strength as high as 63 MPa and Young's modulus being 2.33 GPa, and ease of processability into thin films make the prepared series of polymers good candidates to be successfully applied in opto-electronic devices.
CRIS-Team Scopus Importer:2022-04-14